Perbandingan Kinerja Akurasi Klasifikasi K-NN, NB dan DT pada APK Android - Djarot Hindarto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Today many people use Internet technology, for various needs. Starting from shopping, transportation and education, using the Internet as a digital service. Equipment in accessing the Internet is also many and very diverse, ranging from personal computers, laptops to communication devices such as mobile devices. Today's mobile devices that have quite a lot of variations and are used by the community are mobile devices based on the Android operating system. In this situation, it encourages certain parties to take advantage of loopholes to seek profit, one of which is the creation of Malicious Software (Malware). The existence of Malware is very troubling, where the growth of malware is very fast. The phenomenon of Malware that continues to grow is what makes researchers focus on analyzing Malware by utilizing artificial intelligence technology. The purpose of this study is to analyze Android APK files with the static analysis method and classify the Malware family and not Malware or Normal APK files. Malware and non-Malware APK files were downloaded from Canadian Institute for Cyber ​​Security, Google Play and APK Pure. The files are extracted to be generated and stored as Malware datasets. The malware dataset was trained using machine learning algorithms. Machine learning used is Naïve Bayes, K-Nearest Neighbor and Decision Tree. Performance measurement accuracy and comparison between Naïve Bayes, K-Nearest Neighbor and Decision Tree which is part of Machine Learning.